Fluoroquinolone should be reconsidered as empirical therapy for adult inpatient urinary tract infections in tertiary hospital: a perspective descriptive study from the microbiological and cost-effectiveness aspects - Adhiputra, I Ketut Agus Indra; Setiabudy, Marta (Journal of Clinical Microbiology and Infectious Diseases, 2023)
Background: Urinary Tract Infections (UTI) has become difficult to treat because of its increasing resistance characteristics to antimicrobial agents, especially to fluoroquinolone. The objective of this study was to describe the effectiveness of fluoroquinolone as empirical therapy for adult inpatient UTI. Methods: This descriptive cross-sectional study was performed at Prof. Dr. I.G.N.G. Ngoerah Hospital, a tertiary Hospital in Denpasar, Bali, from January 2020 until March 2020. All urine specimens were examined using bioMérieux VITEK® 2 System. Result: A total of 155 urine samples met the inclusion and exclusion criteria. We found Escherichia coli (39.4%) as the most common microbes followed by Klebsiella pneumoniae (12.3%). Most of the isolates are multi drug resistant organisms (MDRO) (52.9%) and 57% (49) of the Enterobacteriaceae isolates are extended spectrum beta lactamases (ESBLs). The average duration of the empirical antibiotic therapy was 3.7 days for all fluoroquinolone. Ciprofloxacin (53.5%) is the most common empirical therapy, followed by levofloxacin (16.8%). Antimicrobial sensitivity tests showed that bacteria remained highly sensitive to amikacin (96%) and meropenem (94%). The sensitivity test for ciprofloxacin and levofloxacin was only 26% and 4% respectively. The suitability antibiotic results of fluoroquinolone as empirical therapy were only 20% from 110 isolates. The cost ineffectiveness of fluoroquinolone as empirical therapy is Rp.8,402,400 for 3 months. Conclusion: We concluded that both fluoroquinolone (ciprofloxacin and levofloxacin) have a very low sensitivity rate and are not cost-effective, therefore the use of those antimicrobial agents as empirical therapy should be reconsidered.